Variation of excited-state dynamics in trifluoromethyl functionalized C60 fullerenes. Issue 33 (3rd August 2016) - Park, Jaehong; Ramirez, Jessica J.; Clikeman, Tyler T.; Larson, Bryon W.; Boltalina, Olga V.; Strauss, Steven H.; Rumbles, Garry
Abstract : Excited-state studies of trifluoromethyl functionalized C60 fullerenes show the substantial modulation of intrinsic optical properties and excited-state dynamics by the substitution on fullerenes. Abstract : We report on electronically excited-state dynamics of three different trifluoromethyl C60 fullerenes (TMFs, C60 (CF3 ) n :C60/4-1, C60/6-2, andC60/10-1, featuring four, six, and ten trifluoromethyl groups, respectively) using steady-state and time-resolved optical spectroscopy as well as ultrafast pump/probe transient absorption spectroscopy.C60/4-1 andC60/6-2 dissolved in toluene solvent show near-unity S1 → T1 intersystem crossing quantum yield ( Φ ISC ), ca. 1 ns S1 -state lifetimes, and microsecond-timescale T1 -state lifetimes, which are typical of the fullerene class. On the other hand, C60/10-1 exhibits a dominant sub-nanosecond nonradiative S1 → S0 relaxation mechanism and negligible Φ ISC, therefore decreasing the average excited-state lifetime ( τ avg ) by about 5 orders of magnitude compared to that ofC60/4-1 andC60/6-2 ( τ avg ≈ 17 μs and 54 μs forC60/4-1 andC60/6-2, respectively, whereas τ avg ≈ 100 ps forC60/10-1 ). These excited-state characteristics ofC60/4-1 andC60/6-2 are preserved in polymer matrix, suggesting that fullerene/polymer interactions do not modulate intrinsic photophysics of trifluoromethyl-substituted fullerenes. The contrasting excited-state study results ofC60/4-1 andC60/6-2 to that ofC60/10-1 infer that intrinsic optical properties and excited-state dynamics can be affected by the substitution on the fullerene.